Teleconnection of Regional Drought to ENSO, PDO, and AMO: Southern Florida and the Everglades - Anteneh Z. Abiy; Assefa M. Melesse; Wossenu Abtew (Atmosphere, 2019)
Drought variability is associated with global oceanic and atmospheric teleconnections driven by, among others, the Pacific Decadal Oscillation (PDO), the Atlantic Multidecadal Oscillation (AMO), and El Niño−Southern Oscillation (ENSO). Climate teleconnections with a region’s rainfall, with drought and flooding implications, should be part of short- and long-term water management planning and operations. In this study, the link between drought and climatic drivers was assessed by using historical data from 110 years of regional rainfall in southern Florida and the Everglades. The objective was to evaluate historical drought and its link with global oceanic and atmospheric teleconnections. The Standardized Precipitation Index (SPI) assesses regional historical drought in 3-, 6-, 12-, 24-, 36-, 48-, and 60-month periods. Each of the SPIs was used to analyze the association of different magnitudes of drought with ENSO, AMO, and PDO. Historical drought evaluated in different time windows indicated that there is a wet and dry cycle in the regional hydrology, where the area is currently in the wet phase of the fluctuation since 1995 with some drought years in between. Regional historical rainfall anomaly and drought index relationships with each driver and combination of drivers were statistically evaluated. The impact of ENSO fluctuation is limited to short-period rainfall variability, whereas long-period influence is from AMO and PDO.